Vaccine financing and billing in practices serving adult patients: A follow-up survey. Issue 8 (14th February 2018) - Lindley, Megan C.; Hurley, Laura P.; Beaty, Brenda L.; Allison, Mandy A.; Crane, Lori A.; Brtnikova, Michaela; Snow, Megan; Bridges, Carolyn B.; Kempe, Allison
Abstract: Background: Financial concerns are often cited by physicians as a barrier to administering routinely recommended vaccines to adults. The purpose of this study was to assess perceived payments and profit from administering recommended adult vaccines and vaccine purchasing practices among general internal medicine (GIM) and family medicine (FM) practices in the United States. Methods: We conducted an interviewer-administered survey from January-June 2014 of practices stratified by specialty (FM or GIM), affiliation (standalone or ≥ 2 practice sites), and level of financial decision-making (independent or larger system level) in FM and GIM practices that responded to a previous survey on adult vaccine financing and provided contact information for follow-up. Practice personnel identified as knowledgeable about vaccine financing and billing responded to questions about payments relative to vaccine purchase price and payment for vaccine administration, perceived profit on vaccination, claim denial, and utilization of various purchasing strategies for private vaccine stocks. Survey items on payment and perceived profit were assessed for various public and private payer types. Descriptive statistics were calculated and responses compared by physician specialty, practice affiliation, and level of financial decision-making. Results: Of 242 practices approached, 43% (n = 104) completed the survey. Reported payment levels and perceived profit varied by payer type. Only for preferred provider organizations did a plurality of respondents report profiting on adult vaccination services. Over half of respondents reported losing money vaccinating adult Medicaid beneficiaries. One-quarter to one-third of respondents reported not knowing about Medicare Part D payment levels for vaccine purchase and vaccine administration, respectively. Few respondents reported negotiating with manufacturers or insurance plans on vaccine purchase prices or payments for vaccination. Conclusions: Practices vaccinating adults may benefit from education and technical assistance related to vaccine financing and billing and greater use of purchasing strategies to decrease upfront vaccine cost.